Behavior in maintenance actions and the cleanliness level of full acrylic denture bases among the community village: Study observational - Haeruddin, Muhammad Rifaldi; Jubhari, Eri Hendra; Mulyanti, Mulyanti (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
AbstractIntroduction: The maintenance of dentures is an important aspect that varies within communities. According to the 2018 Riskesdas, the prevalence of edentulism in Indonesia shows a rate of 0.9% in urban areas and 1.7% in rural areas. The high rate of edentulism in Polejiwa Village, Malangke Barat District, Luwu Utara, indicates a significant number of complete denture users who often do not receive maintenance instructions from their dentists. This study aims to analyze the maintenance behaviors and cleanliness levels of acrylic dentures among the residents of Village. Methods: TAn analytical observational method with a cross-sectional design was used, involving purposive sampling to select denture users who had their dentures made by a dentist. Data were collected through a questionnaire and cleanliness examinations using the Hoad-Reddick index, which were then analyzed using the Chi-Square test to assess the relationship between maintenance behaviors and cleanliness levels. Results: The study results indicate that 10% of maxillary dentures were classified as clean, while 46.7% were dirty and 43.3% were very dirty. For mandibular dentures, 13.3% were clean, 40% were dirty, and 46.7% were very dirty. The Chi-Square test indicates a significant effect (p-value < 0.05) between maintenance behavior, specifically the frequency of cleaning dentures, and the level of denture cleanliness, with a p-value of 0.001 for the upper jaw and a p-value of 0.000 for the lower jaw. Conclusion: The cleanliness level of acrylic-based dentures in the community of Polejiwa Village is still classified as poor. A significant association was found between the frequency of denture cleaning and the cleanliness levels of both upper and lower jaw dentures in the community of Polejiwa Village.KEYWORDS: Complete dentures, acrylic, hygiene maintenance behavior, denture cleanliness levelPerilaku tindakan pemeliharaan dan tingkat kebersihan gigi tiruan lengkap basis akrilik pada masyarakat desa: studi observasionalABSTRAKPendahuluan: Pemeliharaan gigi tiruan merupakan aspek penting yang berbeda-beda di setiap masyarakat. Berdasarkan Riskesdas 2018, prevalensi edentulous di Indonesia menunjukkan angka 0,9% di daerah perkotaan dan 1,7% di pedesaan. Tingginya angka edentulus di Desa Polejiwa, Kecamatan Malangke Barat, Luwu Utara, mengindikasikan banyak pengguna gigi tiruan lengkap, yang sering kali tidak mendapatkan instruksi pemeliharaan dari dokter gigi. Penelitian ini bertujuan untuk menganalisis perilaku pemeliharaan dan tingkat kebersihan gigi tiruan akrilik di masyarakat Desa. Metode: Metode yang digunakan adalah studi observasional analitik dengan desain cross sectional, melibatkan purposive sampling untuk memilih pengguna gigi tiruan yang dibuat oleh dokter gigi. Data dikumpulkan melalui kuesioner dan pemeriksaan kebersihan menggunakan indeks Hoad-Reddick, yang kemudian dianalisis dengan uji Chi-Square untuk menilai hubungan antara perilaku pemeliharaan dan tingkat kebersihan. Hasil: Penelitian menunjukkan bahwa 10% gigi tiruan maksila berada dalam kategori bersih, sementara 46,7% kotor dan 43,3% sangat kotor. Gigi tiruan mandibula, 13,3% bersih, 40% kotor, dan 46,7% sangat kotor. Analisis Chi-Square menunjukkan adanya pengaruh yang signifikan (nilai p <0.05) antara perilaku pemeliharaan berupa frekuensi pembersihan gigi tiruan dan tingkat kebersihan gigi tiruan, dengan nilai p= 0,001 untuk rahang atas dan nilai p = 0,000 untuk rahang bawah. Simpulan: Tingkat kebersihan gigi tiruan berbasis akrilik pada masyarakat Desa Polejiwa masih tergolong buruk. Ditemukan pengaruh frekuensi pembersihan gigi tiruan terhadap tingkat kebersihan gigi tiruan rahang atas maupun rahang bawah pada masyarakat Desa Polejiwa.KATA KUNCI: Gigi tiruan lengkap, akrilik, perilaku pemeliharaan kebersihan, tingkat kebersihan gigi tiruan